GLUCOSE EXCHANGE DISORDERS IN PATIENTS TAKING GLUCOCORTICOSTEROIDS: FEATURES OF CLINICAL MANIFESTATIONS AND CORRECTION - Al’bert Yu. Selimov; Lyudmila N. Eliseeva; Valeriya P. Kurinnaya; Sergei P. Oranskii (Кубанский научный медицинский вестник, 2019)
The review deals with the problem of carbohydrate metabolism disorders in patients undergoing corticosteroid therapy, relevant for specialists in various fields. The article describes the epidemiology and risk factors for the development of carbohydrate metabolism disorders when using glucocorticosteroids. Contemporary information is provided about the diagnostics, prevalence and pathogenesis of steroid-induced hyperglycemia. A particular attention is paid to current data on various disorders of carbohydrate metabolism in patients with a therapeutic profile. Main approaches to the correction of glycemia in the steroid-induced disorders of carbohydrate metabolism using modern therapy are considered elucidated.Conclusion. The widespread use of glucocorticosteroids, significant prevalence of the steroid-induced disorders of carbohydrate metabolism, features of the pathogenetic mechanisms of steroid-induced diabetes mellitus determine the need to create algorithms for the diagnosis and treatment of these conditions. A conclusion is made that rational glucose-lowering therapy that takes into account the pathogenetic and clinical aspects of the steroid-induced disorders of carbohydrate metabolism, can reduce the rate of macro- and microvascular complications.Conflict of interest: the authors declare no conflict of interest.